2011
DOI: 10.2304/pfie.2011.9.6.686
|View full text |Cite
|
Sign up to set email alerts
|

Breaking into the Movies: Public Pedagogy and the Politics of Film

Abstract: This article argues that how we think about education must extend far beyond matters of schooling and include those spaces, practices, discourses and maps of meaning and affect produced through a range of cultural and pedagogical technologies. We live at a time in which the educational influence of the larger culture has become the major force in producing subjectivities, desires and modes of identification necessary for the legitimation and functioning of a neoliberal society. If pedagogy has become central t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
0
31

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(113 citation statements)
references
References 6 publications
0
82
0
31
Order By: Relevance
“….suggests how important it has become as a site of cultural politics (Giroux, 2001, p. 587). In the view of Giroux, film analysis in the classroom should be "part of a broader circuit of power relations [and] expand the possibilities of multiple readings of texts while making visible how representations work" (p. 53). Activist bell hooks concurs, having found that her students were made more aware of discourses on race, sex, and class through watching films than they had gained from the readings she'd assigned (cited in Giroux, 2001).…”
Section: "Hollywood Hermeneutics" and "Being-in-the-world"mentioning
confidence: 92%
“….suggests how important it has become as a site of cultural politics (Giroux, 2001, p. 587). In the view of Giroux, film analysis in the classroom should be "part of a broader circuit of power relations [and] expand the possibilities of multiple readings of texts while making visible how representations work" (p. 53). Activist bell hooks concurs, having found that her students were made more aware of discourses on race, sex, and class through watching films than they had gained from the readings she'd assigned (cited in Giroux, 2001).…”
Section: "Hollywood Hermeneutics" and "Being-in-the-world"mentioning
confidence: 92%
“…Resulta en cualquier caso llamativo que, siendo el cine un influyente medio de pedagogía pública (Giroux, 2011), se cuestione su valor heurístico. Este escrito emana, por el contrario, del convencimiento de que el relato fílmico, al igual que otros textos académicos no convencionales, es una fuente muy útil para conocer y comprender la realidad social, en este caso, la imagen del profesorado de EF.…”
Section: Premisas Teóricasunclassified
“…As Giroux (2002) opines, media functions as a form of public pedagogy by offering situations and contexts through which viewers can vicariously experience, critique, reflect, and learn about different social phenomena. In their review, Wright and Sandlin noted how popular television shows (e.g., Seinfeld, Buffy the Vampire Slayer) are common and useful narratives to examine representations of adult learning theories.…”
Section: Representations Of Adult Learning and Development In Popularmentioning
confidence: 99%